THE IMPROVEMENT OF STUDENTSâ HIGHER ORDER THINKING IN READING CLASS USING STUDENTSâ RESPONSES TEXTS IN THE THIRD SEMESTER OF ENGLISH EDUCATION PROGRAM PGRI UNIVERSITY OF YOGYAKARTA - Wiyanah, Sri (ELTICS Journal, 2014)
Abstract The research aims to improve the level thinking qualities toward students in Reading III using studentsâ responses text. The research applied descriptive qualitative method. It described about the studentsâ responses text that produced by students in reading novel to improve studentsâ higher order based on their own perspective. The participants of this research were nine students of the semester III, A3 class, English Education Program of PGRI University of Yogyakarta. Data were got through observation, interview, document analysis and questionaire. Qualitative data were anayzed through coding data, explanation, or data presenting and conclusion. The findings showed that using studentsâ responses text in Reading III learning process that focus on novel significantly improve the studentsâhigher order thinking level. The first activities, studentsâorder thinking level still in the lower category i.e., remember and understand. The precentage is only 25%. The second activities, studentsâorder thinking level imrpoved up to 45%. The improvement of studentsâorder thinking in reading comprehension using studentsâ responses also influenced studentsâ motivation and feeling when they were learning. The response text helped students in improving their reading skill. Key words: higher order thinking, reading, studentsâ responses texts